Ancaman Pidana Islam Terhadap Penyalahgunaan Narkoba - Hasan, Hamzah (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2012)
According to Islamic Criminal Law, drug distributors and drug users including other drugs unless for medical reason are part of criminal offence which can be punished within a such law. This clasification is taken from Qiyas in which marijuana and drugs have similar factors as khamar that is “drunk”. For this reason, they have been categorized as “forbideen” (haram) whether a little or a lot because they can destroy people’s mind and phisics as well as other anatomy.